2014
DOI: 10.1002/ppul.23146
|View full text |Cite
|
Sign up to set email alerts
|

Novel outcome measures for clinical trials in cystic fibrosis

Abstract: Cystic fibrosis (CF) is a common inherited condition caused by mutations in the gene encoding the CF transmembrane regulator protein. With increased understanding of the molecular mechanisms underlying CF and the development of new therapies there comes the need to develop new outcome measures to assess the disease, its progression and response to treatment. As there are limitations to the current endpoints accepted for regulatory purposes, a workshop to discuss novel endpoints for clinical trials in CF was he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 143 publications
(207 reference statements)
2
36
0
Order By: Relevance
“…Despite this, FEV 1 presently is used to guide therapy . While other modalities to monitor CF lung disease are emerging, further optimization is required for these complex approaches …”
Section: Introductionmentioning
confidence: 99%
“…Despite this, FEV 1 presently is used to guide therapy . While other modalities to monitor CF lung disease are emerging, further optimization is required for these complex approaches …”
Section: Introductionmentioning
confidence: 99%
“…Other outcome measures might be used to assess effects of airway clearance . These include imaging techniques (eg, 3 He‐MRI, nuclear medicine clearance scans) or other pulmonary function measures (eg, multiple breath washout).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of lung ventilation by these MRI techniques will be especially relevant in young children with CF, where traditional effort‐dependent measures of lung function, that is, forced expiratory volume in 1 sec (FEV 1 ) are not applicable or insensitive to detect early impairment of lung function . In contrast to spirometry, recent studies demonstrated that the multiple‐breath washout technique is sensitive to detect global ventilation inhomogeneity from early childhood in patients with CF .…”
Section: Mri Of Cf Lung Disease: Visualization Of Morphology Perfusimentioning
confidence: 99%
“…In addition to early diagnosis by CF newborn screening that is now accomplished in most Western countries, sensitive non‐invasive outcome measures of lung disease that are applicable for early detection and life‐long monitoring of disease progression and effects of therapeutic interventions in the clinical setting will be instrumental to exploit this unique window of opportunity and reduce current barriers to normalcy in future generations of people with CF . In this context, cross‐sectional lung imaging offers the advantage that it can be performed reliably from infancy and that it provides information on the nature and regional distribution of abnormalities that cannot be captured by global measurements of lung function such as spirometry or multiple breath washout . However, despite its superior sensitivity to detect mild structural lung disease (i.e., early bronchiectasis and air trapping), and emerging feasibility to reduce radiation exposure by iterative reconstruction as well as very fast acquisition times, the use of CT imaging for early detection and long‐term monitoring has the disadvantage of cumulating dose of ionizing radiation that comes with a residual risk of malignancies later in life .…”
Section: Introductionmentioning
confidence: 99%